Portfolio planning and risk management in the pharmaceutical industry 1 - Greuel, Joachim M. (Henry Stewart Talks, 2017)
Portfolio management in pharmaceutical R&D and industry, Best practice portfolio management in big pharma, Evaluation of individual projects, The five determinants of value, Net Present Value (NPV) equation, Financial project evaluation, Sources of risk, How to calculate NPVs, Attrition rates & reasons for failure in R&D, R&D risk management, Commercial risks, Sales forecast (15 trials in Monte Carlo simulation), Monte Carlo simulation: frequency histogram, Added value per completed milestone, Getting to valid assumptions and good decisions